A FRAMEWORK FOR SMART DAIRY INDUSTRY: TECHNOLOGICAL & ORGANISATIONAL ASPECT - Smiti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The research demonstrates the development of a framework for improvement in the dairy industry using technological and organizational domains concerning Industry 4.0. The technological domain includes smart factories, smart operations, smart products, and data-driven services. On the other hand, the organizational domain includes two factors: employees and cyber security. The proposed framework will benefit the establishment of a new Dairy industry concerning Industry 4.0. Structural equation modeling (SEM) has been applied to all six latent factors namely smart factory, smart operations, smart product, data-driven services, employees, and cyber security to evaluate the interrelationship of factors. In the research work, Exploratory factor analysis (EFA) was carried out using the Principal Component Analysis (PCA) to interpret the constructs before taking up Confirmatory factor analysis (CFA). Then, using AMOS software, all the latent variables were examined to determine how well the indices fit the theory. In the end, the approach produced structural equation modeling (SEM), which goodness of fit statistics was used to assess.